A new GNPAT variant of foetal rhizomelic chondrodysplasia punctata. Issue 8 (10th June 2021) - Cordisco, Adalgisa; Pelo, Elisabetta; Di Tommaso, Mariarosaria; Biagiotti, Roberto
Abstract: Background: Rhizomelic chondrodysplasia punctata (RCDP) is a clinical entity resulting from defects of peroxisomal metabolism whose clinical phenotype is characterized by rhizomelia, calcified foci in periarticular cartilage, coronal lesions of vertebral bodies, cataracts and severe cognitive delay. Usually, survival does not exceed the first decade of life. Transmission is autosomal recessive and is related to mutations in the PEX7, GNPAT or AGPS . Methods: A detailed description of the prenatal ultrasound signs of RCDP found in two successive pregnancies in a consanguineous couple is reported. Molecular genetic investigations included the study of the coding regions and the exon–intron junctions of the GNPAT (high‐throughput amplification and sequencing performed with Roche NimbleGen SeqCap Target kit on Illumina platform); the confirmation test was carried out by amplification and Sanger sequencing with automatic capillary sequencer. Results: In addition to the typical prenatal ultrasound signs described in the literature in association with RCDP, the presence of prefrontal oedema, never previously described, has been detected in both pregnancies. Moreover, genetic investigations have found a new splicing variant c.924+1G>A of the homozygous GNPAT . Conclusion: The role of mutation in the GNPAT suggests a likely association with the clinical phenotype. Abstract : Rhizomelic chondrodysplasia punctata (RCDP) is a rare developmental disorder, characterized by rhizomelic bone shortening and epiphyseal stippling, microcephaly, characteristic facial features and severe psychomotor retardation. Transmission is autosomal recessive and is related to mutations in the PEX7, GNPAT or AGPS genes. A fetal diagnosis of RCDP with a new mutation of the GNPAT gene is reported.